2016
DOI: 10.1016/j.psychres.2016.07.048
|View full text |Cite
|
Sign up to set email alerts
|

The optimisation of experience sampling protocols in people with schizophrenia

Abstract: Experience sampling methodology (ESM) involves completing questionnaires during daily life and has been used extensively in people with schizophrenia to assess symptoms and behaviours. Despite considerable advantages over interview measures, there is limited information about its external validity. Our aim is to investigate whether ESM protocol implementation is affected differentially in people with schizophrenia and healthy individuals by factors such as mood, medication and symptoms which would have implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…However, previous research has shown that the ESM is a feasible, reliable, and valid assessment method in various populations. 16,17,30,47 Applying this method enabled us to study the interplay of psychological processes in everyday life where these processes and their association with PE naturally occur.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…However, previous research has shown that the ESM is a feasible, reliable, and valid assessment method in various populations. 16,17,30,47 Applying this method enabled us to study the interplay of psychological processes in everyday life where these processes and their association with PE naturally occur.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Yet, preliminary research supports the short-term feasibility and acceptability of EMA in psychosis via mobile devices [13, 14]. Various studies show that people with schizophrenia accept and can be trained to use EMA and that compliance is comparable to that of nonclinical populations [14-19]. Notably, EMA has demonstrated incremental validity over traditional retrospective reports in assessing symptoms associated with schizophrenia [18, 20].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has shown that the ESM is a feasible, reliable, and valid assessment method in various populations [16,17,31,48].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Interview [48] was used to measure experiences of bullying. This inventory consists of 84 items covering physical, verbal, and indirect forms of bullying during primary school and high school.…”
Section: Experiences Of Bullying An Amended Questionnaire Version Ofmentioning
confidence: 99%
See 1 more Smart Citation